The Role of Platelet and its Interaction with Aspirin - Luisa Fernanda Zúñiga Cerón; Jann Sebastián Saavedra Torres; Carlos Alberto Navia Amézquita (Revista de la Facultad de Medicina, 2016)
Introduction. Platelets are not strictly “cells”, they are cytoplasmic fragments that are produced by the division of the cytoplasm of the megakaryocytes in the bone marrow; among its properties of adhesion and aggregation, platelets are involved in primary hemostasis, thrombosis, repair and tissue regeneration processes. To modify the pro-thrombotic platelet properties aspirin (ASA) is provided, which allows blocking the synthesis of prostaglandins in order to irreversibly inhibit the COX1 and prevent platelet aggregation. The current guidelines govern the use of aspirin in the prevention of cardiovascular diseases. Objective. In this review paper graphics were created to facilitate the understanding of platelets and its interaction with various physiological and pathological processes. Methodology. A literature review of a total of 74 documents such as articles and books was carried out; it was obtained from bibliographic searches in the following databases: Scielo, NEJM, Elsevier, Pubmed, Redalyc, Wiley, Springer, ScienceDirect, BVS, Nature Riviews, EBSCO, Naxos (databases offered by the University of Cauca). Mendeley free access program was used for the management and organization of information. Conclusion. It is recognized the role of platelet in different physiopathological processes and thus its interaction with aspirin, preventing its aggregation and thrombus formation in the spleen and other organs, this way contributing to the prevention of future cardiovascular events.